Renewing Dialogues in Marxism and Education
IX, 293 p.
Keywords: In the first book in their series on Marxism and Education, Rikowski and Green use Marxist theory to examine the dialectic between race and power in education. The series is aimed at educationalists - teachers, researchers, policy-makers or administrators, as well as activists who consider the Marxist tradition a valuable and important resource.